Gut Microbiota and Neuroinflammation in Acute Liver Failure and Chronic Liver Disease - Lucia Giuli; Marta Maestri; Francesco Santopaolo; Maurizio Pompili; Francesca Romana Ponziani (Metabolites, 2023)
Acute liver failure and chronic liver disease are associated with a wide spectrum of neurological changes, of which the best known is hepatic encephalopathy (HE). Historically, hyperammonemia, causing astrocyte swelling and cerebral oedema, was considered the main etiological factor in the pathogenesis of cerebral dysfunction in patients with acute and/or chronic liver disease. However, recent studies demonstrated a key role of neuroinflammation in the development of neurological complications in this setting. Neuroinflammation is characterized by activation of microglial cells and brain secretion of pro-inflammatory cytokines, such as tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and IL-6, which alter neurotransmission, leading to cognitive and motor dysfunction. Changes in the gut microbiota resulting from liver disease play a crucial role in the pathogenesis of neuroinflammation. Dysbiosis and altered intestinal permeability, resulting in bacterial translocation and endotoxemia, are responsible for systemic inflammation, which can spread to brain tissue and trigger neuroinflammation. In addition, metabolites derived from the gut microbiota can act on the central nervous system and facilitate the development of neurological complications, exacerbating clinical manifestations. Thus, strategies aimed at modulating the gut microbiota may be effective therapeutic weapons. In this review, we summarize the current knowledge on the role of the gut–liver–brain axis in the pathogenesis of neurological dysfunction associated with liver disease, with a particular focus on neuroinflammation. In addition, we highlight emerging therapeutic approaches targeting the gut microbiota and inflammation in this clinical setting.